2009
DOI: 10.1111/j.1365-2486.2009.01845.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ecosystem warming on boreal black spruce bud burst and shoot growth

Abstract: The boreal forest is predicted to experience the greatest warming of any forest biome during the next 50-100 years, but the effects of warming on vegetation phenology are not well known. The objectives of this study were to (1) examine the effects of whole ecosystem warming on bud burst and annual shoot growth of black spruce trees in northern Manitoba, Canada and (2) correlate bud burst to cumulative degree-days (CDD). The experimental design was a complete randomized block design that consisted of four repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
59
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 34 publications
8
59
0
1
Order By: Relevance
“…According to the simulations, the onset of the growing season shifted by 7 days from 14 June to 7 June between the 1950-1970and 1990. This result is consistent with the study of Bronson et al (2009) on the effect of warming on black spruce budburst. During phase 3, which corresponds to budburst, a portion of the available carbon simulated by MAIDEN comes from stored non-structural carbohydrates that are from the current and previous years (parameter Cbud; see Table 1).…”
Section: Mechanistic and Regression-based Diagnosticssupporting
confidence: 82%
See 1 more Smart Citation
“…According to the simulations, the onset of the growing season shifted by 7 days from 14 June to 7 June between the 1950-1970and 1990. This result is consistent with the study of Bronson et al (2009) on the effect of warming on black spruce budburst. During phase 3, which corresponds to budburst, a portion of the available carbon simulated by MAIDEN comes from stored non-structural carbohydrates that are from the current and previous years (parameter Cbud; see Table 1).…”
Section: Mechanistic and Regression-based Diagnosticssupporting
confidence: 82%
“…However, because we added a mechanism to smooth yearly variations (see the day23_flex parameter), more years were needed by the plants to acclimate to variable GDD accumulations in winter-spring. With the selected parameters to simulate stem growth, the median onset of the growing season was 10 June (similar to observations for black spruce in northern Mani- toba, Canada; Bronson et al, 2009), with a standard deviation of 7.8 days. If the smoothing term was excluded, then the standard deviation increased to 9.4 days (see Fig.…”
Section: Mechanistic and Regression-based Diagnosticsmentioning
confidence: 99%
“…Independently of year, bud burst started on average on DOY 150 and soil warming didn't affect the onset. Considering the similar photoperiod between the two sites, air temperature probably plays a predominant role in determining the initiation of bud development in SIM, confirming the finding of Bronson et al (2009). Overall, independently of study site, the bud burst process lasted longer in 2013 than 2012, 3 and 6 days more on average at BER and SIM, respectively.…”
Section: Soil Temperature and Bud Burstsupporting
confidence: 74%
“…Although in the short-term a previous study revealed that a 5 °C increase in the soil temperature does not significantly affect the onset of bud burst and the shoot growth of 12 years old black spruce trees, from the third year of treatment the final shoot length showed an increase in the order of 14% (Bronson et al, 2009).…”
Section: Soil Temperature and Bud Burstmentioning
confidence: 99%
See 1 more Smart Citation